Portrait Gender Inequality in Indonesian Family Law : A Perspective Constitution Maternal and Child Welfare (MCH) 2024 and Decision Court Related - Chandra, Mardi (CV. Era Digital Nusantara, 2025)
This article analyzes gender inequality in Indonesian family law through the lens of the 2024 Law on Maternal and Child Welfare (KIA Law) and related court decisions. Although the KIA Law grants mothers six months of leave and fathers two days, its implementation still reflects gender inequality. Decisions by the Supreme Court and the Constitutional Court indicate efforts to balance rights and responsibilities within the family. However, patriarchal norms continue to influence family law practices. This article employs a normative juridical approach and case studies to evaluate the effectiveness of the KIA Law in achieving gender equality.